Azodicarboxylate-free esterification with triphenylphosphine mediated by flavin and visible light: method development and stereoselectivity control. Issue 36 (11th September 2018) - März, Michal; Kohout, Michal; Neveselý, Tomáš; Chudoba, Josef; Prukała, Dorota; Niziński, Stanislaw; Sikorski, Marek; Burdziński, Gotard; Cibulka, Radek
Abstract : Photoredox catalysis: A new way to induce triphenylphosphine to be able to mediate nucleophilic substitution reactions of alcohols and acids. Abstract : Triphenylphosphine (Ph3 P) activated by various electrophiles ( e.g., alkyl diazocarboxylates) represents an effective mediator of esterification and other nucleophilic substitution reactions. We report herein an aza-reagent-free procedure using flavin catalyst (3-methyl riboflavin tetraacetate), triphenylphosphine, and visible light (448 nm), which allows effective esterification of aromatic and aliphatic carboxylic acids with alcohols. Mechanistic study confirmed that photoinduced electron transfer from triphenylphosphine to excited flavin with the formation of Ph3 P˙ + is a crucial step in the catalytic cycle. This allows reactive alkoxyphosphonium species to be generated by reaction of an alcohol with Ph3 P˙ + followed by single-electron oxidation. Unexpected stereoselectivity control by the solvent was observed, allowing switching from inversion to retention of configuration during esterification of ( S )- or ( R )-1-phenylethanol; for example with phenylacetic acid, the ratio shifting from 10 : 90 (retention : inversion) in trifluoromethylbenzene to 99.9 : 0.1 in acetonitrile. Our method uses nitrobenzene to regenerate the flavin photocatalyst. This new approach to flavin re-oxidation has also been successfully proved in benzyl alcohol oxidation, which is a "standard" process among flavin-mediated photooxidations.